2017
DOI: 10.1126/science.aao1887
|View full text |Cite
|
Sign up to set email alerts
|

A high-coverage Neandertal genome from Vindija Cave in Croatia

Abstract: To date the only Neandertal genome that has been sequenced to high quality is from an individual found in Southern Siberia. We sequenced the genome of a female Neandertal from ~50 thousand years ago from Vindija Cave, Croatia to ~30-fold genomic coverage. She carried 1.6 differences per ten thousand base pairs between the two copies of her genome, fewer than present-day humans, suggesting that Neandertal populations were of small size. Our analyses indicate that she was more closely related to the Neandertals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
812
5
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 585 publications
(925 citation statements)
references
References 109 publications
41
812
5
9
Order By: Relevance
“…In individual populations, coverage ranges from 382 Mb in Peruvians (PEL) to 655 Mb in Bengalis (BEB), and the average proportion of haplotypes carrying a detected segment at a position ranges from 0.80% in Puerto Ricans (PUR) to 1.23% in Han Chinese (CHB and CHS) (Figure 3). These detection rates are around half of the estimated introgression proportions obtained using f 4 -ratio statistics (Prufer et al, 2017). This is in line with the simulation results, in which half the introgressed material can be detected, while the other introgressed segments are too short for confident detection.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In individual populations, coverage ranges from 382 Mb in Peruvians (PEL) to 655 Mb in Bengalis (BEB), and the average proportion of haplotypes carrying a detected segment at a position ranges from 0.80% in Puerto Ricans (PUR) to 1.23% in Han Chinese (CHB and CHS) (Figure 3). These detection rates are around half of the estimated introgression proportions obtained using f 4 -ratio statistics (Prufer et al, 2017). This is in line with the simulation results, in which half the introgressed material can be detected, while the other introgressed segments are too short for confident detection.…”
Section: Resultsmentioning
confidence: 79%
“…High coverage reference genomes for the Altai Neanderthal, Altai Denisovan and Vindija 33.19 Neanderthal (Prufer et al, 2017) were obtained from http://cdna.eva.mpg.de/neandertal/Vindija/. Most of the analyses in this study were conducted prior to the publication of the Vindija 33.19 genome, and hence most Neanderthal-based analyses use the Altai Neanderthal rather than the Vindija 33.19 Neanderthal.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases save for rs115978361, the SNPs in the ROI are uniquely derived in humans as compared to other primates and archaic hominins, and are present in more than one individual in the 1000G and HGDP data (Table 2). No SNPs are present in the ROI in a sample of 10 chimpanzees (Auton et al, 2012) and no fixed substitutions are present compared to three archaic hominins (Meyer et al, 2012; Prüfer et al, 2014, 2017) across the entire 2251 bp region. There is one fully derived site in our human samples that is heterozygous in the Altai Neanderthal (chr7:114288583) and 9 fixed differences compared to the PanMap chimps (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…A few years later, a high coverage genome sequence from a Neanderthal found in the Altai mountains allowed researchers to pin down the proportion of Neanderthal ancestry in non-Africans to be ~2% [4] . In 2017, a second high coverage genome sequence from a Neanderthal in Croatia showed that this individual was more closely related to the introgressing Neanderthal population than the Altai Neanderthal, allowing researchers to detect even slightly higher levels of Neanderthal DNA [5] . In 2018, low-coverage genomes of five additional Neanderthals living between 39,000 and 47,000 years ago allowed a first glimpse at population structure in Neanderthals and showed indications of population turnover in late Neanderthal history [6] .…”
Section: Genome-wide Patterns Of Archaic Admixturementioning
confidence: 99%